Impact of Online Gambling Practices on Family Harmony: A Case Study in South Meruya, Kembangan Sub-District, West Jakarta - Ramadhan, Taufiq; Taufik, Taufik; Mubarok, Tb. Azka; Arif Mahendra, Bayu (Qanun: Jurnal Hukum Keluarga Islam, 2024)
This article aims to examine the implications for household harmony of the practice of online gambling. Then this research is aimed at examining how the background causes someone to fall into online gambling and examining the consequences of gambling games on people who are married. The phenomenon of online gambling practices has recently been found in the Meruya Selatan area, Kembangan District, West Jakarta, which is dominated by teenagers and some are married. The type of research used in this writing is qualitative research that produces descriptive data analysis, supported by primary and secondary data sources then data collection techniques by means of observation, interviews and documentation. The results of this study show that the causes of online gambling are due to several factors, namely cultural factors, economic factors, situational factors and technological development factors. As for the consequences caused to households that are involved in online gambling, namely resulting in divorce, quarrels, unpaid debts and emotions that quickly rise and are not controlled.